Student Internships and Employment Opportunities after Graduation: A Field Experiment - Stijn Baert; Brecht Neyt; Thomas Siedler; Ilse Tobback; Dieter Verhaest (Institute of Labor Economics (IZA), 2019)
Internships during tertiary education have become substantially more common over the past decades in many industrialised countries. This study examines the impact of a voluntary intra-curricular internship experience during university studies on the probability of being invited to a job interview. To estimate a causal relationship, we conducted a randomised field experiment in which we sent 1,248 fictitious, but realistic, resumes to real job openings. We find that applicants with internship experience have, on average, a 12.6% higher probability of being invited to a job interview.
Keywords: C93; I21; J23; J24; 330; internship; hiring; human capital; signalling; field experiment